2016
DOI: 10.1002/pbc.26027
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Social Outcomes of Hyperfractionated Radiation on Childhood ALL Survivors

Abstract: Long-term social outcomes were better among ALL survivors who received HFX than CFX. A wider study involving all patients enrolled on DFCI 87-01/91-01 protocols should be conducted to reconsider radiation protocols for ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Fourth, separate analysis of certain patient populations is essential to reduce selection bias. Many prior studies that found difficulties among patients included brain tumor survivors or those with acute lymphoblastic leukemia who received cranial radiation at a young age . Our study excluded these patient populations, which removes this as a confounding factor and is supported by a lack of difference in estimated IQ between our groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fourth, separate analysis of certain patient populations is essential to reduce selection bias. Many prior studies that found difficulties among patients included brain tumor survivors or those with acute lymphoblastic leukemia who received cranial radiation at a young age . Our study excluded these patient populations, which removes this as a confounding factor and is supported by a lack of difference in estimated IQ between our groups.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, some of the earlier studies that suggested difficulties evaluated patients treated in the 1970s and 1980s prior to widespread use of supportive care measures (ie, central lines, anti‐emetics, child life specialists, and conscious sedation for procedures) that have reduced patient's fear and improved quality of life . Lastly, the use of cranial radiation has decreased given the known neurocognitive effects, especially in the prophylactic setting for leukemia …”
Section: Introductionmentioning
confidence: 99%